Strategi Pemerintahan Desa Tridaya Sakti Dalam Pencegahan Penyebaran Dan Edukasi Covid-19 - Yoga Trie Hapiyan; Haura Atthahara; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The existence of the corona virus (COVID-19) pandemic has forced both central and regional governments to have to think of strategies to prevent its spread. Even though the health protocols have been implemented, in practice there are still people who violate and even ignore the dangers of this virus. Therefore, further strategies are needed to overcome this. In Tridaya Sakti village, the strategy is to solidify between residents, RT, RW, babinsa, kamtibmas, and village officials. Some activities such as social worship, culture are limited by the provisions of health protocols. However, the obstacles to handling covid in Tridaya Sakti village, there are often crowds who do not comply with health protocols and do not obey the rules of opening hours during the pandemic, and there are still people who are not aware of the health protocols so that the task force or task force must intervene to educate the dangers of COVID -19.